Geometric and dimensional characteristics of simulated curved canals prepared with proTaper instruments - Renata de Castro Martins; Maria Guiomar de Azevedo Bahia; Vicente Tadeu Lopes Buono (Journal of Applied Oral Science, 2010)
OBJECTIVE: This study identified which regions of ProTaper instruments work during curved root canal instrumentation. MATERIAL AND METHODS: Twelve ProTaper instruments of each type, S1, S2, F1, and F2, were assessed morphometrically by measuring tip angle, tip length, tip diameter, length of each pitch along the cutting blades, and instrument diameter at each millimeter from the tip. Curved canals in resin blocks were explored with manual stainless steel files and prepared with ProTaper instruments until the apical end following four distinct sequences of instrumentation: S1; S1 and S2; S1, S2, and F1; S1, S2, F1, and F2. Image analysis was employed for measuring canal diameters. The diameters of the canals and diameters of the instruments were compared. Data were analyzed by one-way ANOVA and Tukey's test. RESULTS: No statistically significant difference was found between the canals and instrument diameters (p>0.05). The largest diameters in the end-point of the instrumented canals were obtained with F1 and F2 instruments and in the initial and middle thirds with S1 and S2 instruments. CONCLUSIONS: All instruments worked at the tip and along their cutting blades, being susceptible to fail by torsion, fatigue, or the combination of these two mechanisms.